Edukasi Artificial Intelligence Untuk Meningkatkan Literasi Digital Pelajar - Monika Budiman; Marini Anggie Putri Siregar; Lydia Kurniawan; Swesti Mahardini; Aang Syahdina; Malik Hidayat (Universitas Perjuangan Tasikmalaya, 2026)
The advancement of Artificial Intelligence (AI) technology presents significant opportunities in the field of education, particularly in enhancing the effectiveness of teaching and learning processes. However, many educators and students still lack understanding of how to utilize AI optimally and ethically. This community service program aimed to improve teachers’ and students’ knowledge and skills in using AI technologies, especially language-based models such as ChatGPT, as tools to support interactive learning. The implementation method included socialization, training sessions, and direct mentoring to help participants understand the basic concepts of AI and how to integrate them into learning activities. The results showed an increase in participants’ understanding of the functions and potential of AI in education, along with growing awareness of the importance of using this technology wisely and ethically. In conclusion, this program successfully enhanced digital literacy and encouraged the use of AI as an innovative learning approach aligned with the spirit of the Merdeka Belajar (Freedom to Learn) policy.